Day 1 Wed, April 18, 2018 2018
DOI: 10.2118/191322-ms
|View full text |Cite
|
Sign up to set email alerts
|

Bond Strength Between Different Casing Materials and Cement

Abstract: It is common practice to use steel casing when constructing and completing oil wells. However, well integrity issues caused by corrosion require well intervention operations which increase the non-productive time. This has led to investigations by researchers and engineers to improve the corrosion resistance of steel by modifying alloying elements. Some other researchers have suggested the use of aluminum alloy casing because of its resistance to corrosive H2S environments, and its lightweight characteristics.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 15 publications
1
9
1
Order By: Relevance
“…The shear bond strength of class G cement at the pipe interface was only 17% of the bond strength with the bar. In another study with the same cement and similar grade of steel bar in the middle, Khalifeh et al [14] reported the shear bond strength of 1.3 MPa, which is 58% lower than the current measured strength. Following sample preparation procedure but increasing temperature by 20°C and curing under elevated pressure of 3.4 MPa has positively impact shear bond strength.…”
Section: Resultscontrasting
confidence: 73%
See 3 more Smart Citations
“…The shear bond strength of class G cement at the pipe interface was only 17% of the bond strength with the bar. In another study with the same cement and similar grade of steel bar in the middle, Khalifeh et al [14] reported the shear bond strength of 1.3 MPa, which is 58% lower than the current measured strength. Following sample preparation procedure but increasing temperature by 20°C and curing under elevated pressure of 3.4 MPa has positively impact shear bond strength.…”
Section: Resultscontrasting
confidence: 73%
“…The compatibility of the casing material and the cementitious slurry is a necessity. In an earlier experimental study conducted by Khalifeh et al [14], incompatibility of aluminum pipe and the API neat class G cement was highlighted. Steel pipes are common materials for casing the borehole.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Hydraulic bond strength failure may eventuate from shrinkage or expansion of plugging material or expansion of casing caused by reservoir pressure build-up and/or due to interaction in the interface of casing and plugging material [14].…”
Section: Bondingmentioning
confidence: 99%